Discoid subacute lupus erythematosus and anorexia. - Pisani, V. (European Journal of Pediatric Dermatology, 2011)
Case report. A 13-year-old girl reported lesions in sun-exposed areas worsening in summer. Last summer the lesion worsened again and anorexia appeared. Currently the patient weighed 37 kg, was 1.58 high and was not menstruating. The physical examination highlighted on the face, décolleté and back of hands erythematous, hyperkeratotic lesions with clear-cut borders, without atrophy. Laboratory tests, including nonspecific inflammatory indexes, were normal except for C3 0.89 g / L (n.v. 0.90 to 1.8); autoantibodies were not detected. Histology showed hyperparakeratosis, vacuolization of the basal layer and perivascular lymphocytic infiltrate, compatible with subacute lupus erythematosus. The final diagnosis was discoid/subacute lupus erythematosus, exposure to sunlight was not recommended, topical corticosteroids were prescribed and the patient was sent in psychiatry, postponing antimalarial therapy.